Drivers Behind the Financial Insolvency: An Empirical Study on the Textile Industry in Bangladesh - Rezina, Sonia; Mostofa, Md Shahnawaz (The Economics and Finance Letters, 2020)
The main purpose of the research study is to assess the financial soundness of the textile industry in Bangladesh. The effects of financial ratios have also been examined. The research has been designed based on published quantitative data in the stock market. 35 listed companies that consist of A-Category, B-Category and Z-category companies were analyzed. In this research study, five financial ratios have been analyzed and tested using the Altman Z-score model. Statistical correlation among the financial ratio was examined to depict the picture of financial distress among the different categories of companies in Textile industries in Bangladesh. Most of the A category companies are in Safe Zone or financially sound, B category companies are into Grey Zone and Z category companies are in distress zone. The outcome of the study can be valuable for the financial managers to take important managerial as well as financial decisions, the shareholders to take appropriate investment decisions and bankers to evaluate the prospective borrowers’ credit risk and renew loans of the concerned textile manufacturers of the country.